The Integrated Processing Method of Educational Information Resources Based on Edge Computing. (20th May 2022) - Lv, Zhimei
Abstract : Due to the development of information technology, the new type of smart campus integrated teaching, scientific research, office services, and many other applications, online education information resources show a blowout growth. However, huge amounts of data to the campus network carrying capacity put forward high requirements. With the help of edge computing and cloud computing platform and network, the teaching, scientific research, office services, and many other applications of big data integration mining analysis build intelligent management, teaching, scientific research, and life mode, to improve the utilization of education information resources. Improving the school management level and education quality is imperative. The research purpose of this paper is to study the integrated processing method of educational information resources based on edge computing. The research of this paper enriches the relevant optimization theory of edge computing on the one hand and provides reference for the practical integrated processing of practical educational information resources on the other hand, which has the dual significance of theory and practice.